EFFECTIVENESS OF ACUPUNCTURE IN THE TREATMENT OF CHRONIC LOW BACK PAIN (LBP): LITERATURE REVIEW - Taqi, Muhammad Bariq; Rianzie, Raissa; Pinta Gracia, Regina; Salsabila; Septadina, Indri Seta (International Journal of Islamic and Complementary Medicine, 2024)
Chronic Low Back Pain (CLBP) or Low Back Pain (NPB) is pain between the costal and gluteal margins that persists for over three months. LPB is a common disease. Fifty percent of the world's population is estimated to experience LBP by 30, and 70% of the population will experience LBP at some point in their adulthood. There is no gold standard for LBP therapy, so the therapy needed depends on the patient. One of the therapies used is acupuncture therapy. In a randomized clinical trial, acupuncture therapy demonstrated greater effectiveness in reducing pain intensity for patients with chronic LBP compared to administering oral baclofen at a dose of 30 mg/day. Another study in Germany with 1162 research subjects also found that providing acupuncture therapy in the treatment of chronic LBP had more significant efficacy on the patient's pain and functional status than conventional therapy.